1996
DOI: 10.1063/1.472527
|View full text |Cite
|
Sign up to set email alerts
|

Unimolecular decomposition of NO3: The NO+O2 threshold regime

Abstract: The unimolecular decomposition of expansion-cooled NO3 has been investigated in the threshold regime of the NO+O2 channel. Photoexcitation in the region 16 780–17 090 cm−1 (596–585 nm) prepares ensembles of molecular eigenstates, each of which is a mixture of the B 2E′ bright state and lower electronic states. The X 2A2′ ground state is believed to be the probable terminus of 2E′ radiationless decay, though participation of A 2E″ is also possible. For these photon energies, unimolecular decomposition occurs ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 41 publications
8
42
0
Order By: Relevance
“…A relatively recent study 4 of the absorption spectrum of jetcooled NO 3 permitted resolution of structure in the band origin and supported the occurrence of vibronic coupling with levels of the ground state. Other studies [5][6][7] confirmed that NO 3 is strongly predissociated in higher levels of its B state. Because of the prominence and distinctive position of the band origin, it has often been used to map the behavior of NO 3 in gas-phase reaction systems.…”
Section: Introductionmentioning
confidence: 60%
“…A relatively recent study 4 of the absorption spectrum of jetcooled NO 3 permitted resolution of structure in the band origin and supported the occurrence of vibronic coupling with levels of the ground state. Other studies [5][6][7] confirmed that NO 3 is strongly predissociated in higher levels of its B state. Because of the prominence and distinctive position of the band origin, it has often been used to map the behavior of NO 3 in gas-phase reaction systems.…”
Section: Introductionmentioning
confidence: 60%
“…CS/Ag + ion composite film shows a new band about 821 cm -1 assigned to NO 3 -absorption, which confirms the existence of NO 3 -as a residual ion from silver salt. Such band is not observed in CS/AgNP films, likely due to thermal decomposition of NO 3 to NO and O 2 [46]. …”
Section: Ftir Analysismentioning
confidence: 67%
“…Another possible reaction is unimolecular decomposition of NO 3 at irradiation stages. Indeed, a reaction NO 3 -NO þO 2 is well known from atmospheric chemistry (Davidson et al, 1990;Mikhaylichenko et al, 1996) and it leads to generation of the products being non-detectable by EPR method. However, it is not clear, whether such a reaction occurs at low temperatures.…”
Section: Generation Of Radicals Under Irradiationmentioning
confidence: 99%